Implementasi Kebijakan Pemerintah Daerah Dalam Penataan Pedagang Kaki Lima - Roja, Rahtia San Khusnu; Hikmawati, Ikeu (Media Hukum Indonesia (MHI), 2024)
This research aims to determine the implementation of Garut Regency regional government policy in managing street vendors in the Pengkolan area and the factors that hinder it. Using qualitative methods with descriptive analysis. Where data collection used includes observation, interviews and documentation. Data analysis techniques using data reduction, data presentation and drawing conclusions. The results of the research concluded that the local government had communicated to street vendors both persuasively and repressively. Human resources implementing policies are ready in quality and quantity to carry out their duties and functions. Meanwhile, equipment resources are still limited and cannot accommodate a large number of street vendors. Limited budget is a problem for relocating street vendors from red zones. The policy implementers already have a strong attitude and commitment to implementing government policies in structuring street vendors in the Pengkolan area. The arrangement of street vendors in the Pengkolan area has involved various related agencies and stake holders. In the field, factors found to be obstacles were the government's lack of seriousness in enforcing criminal and civil sanctions, the lack of awareness of street vendors regarding the rules and the reluctance of street vendors to be relocated.